A study and Implementation of a controller used in a full-bridge inverter of distributed generation systems (Journal of the College of Basic Education, 2022)
In this work we study one of single phase control way to be used in low and medium power systems. These power systems used in designing solar and wind energy sources. As examples the hybrid vehicles , solar houses and hospitals that need clean , efficient and steady state energy sources. Moreover, the size and mass of these inverters reduce available vehicle storage space. An ideal solution is to provide a small inverter for each battery, so that its charge can be maintained individually and a low-distortionsine wave can be applied to the motor. A battery charger is then intrinsic in this layout. This work presents the development and implementation of a such a multilevel inverter. Two separate designs are constructed, each including a master module and six slave modules. A battery charger is then intrinsic in this layout. Two separate designs are constructed, each including a master module and six slave modules.